Genetic risk factors for eating disorders: an update and insights into pathophysiology - Hubertus Himmerich; Jessica Bentley; Carol Kan; Janet Treasure (SAGE Publishing, 2019)
Genome-wide-association studies (GWASs), epigenetic, gene-expression and gene-gene interaction projects, nutritional genomics and investigations of the gut microbiota have increased our knowledge of the pathophysiology of eating disorders (EDs). However, compared with anorexia nervosa, genetic studies in patients with bulimia nervosa and binge-eating disorder are relatively scarce, with the exception of a few formal genetic and small-sized candidate-gene-association studies. In this article, we review important findings derived from formal and molecular genetics in order to outline a genetics-based pathophysiological model of EDs. This model takes into account environmental and nutritional factors, genetic factors related to the microbiome, the metabolic and endocrine system, the immune system, and the brain, in addition to phenotypical traits of EDs. Shortcomings and advantages of genetic research in EDs are discussed against the historical background, but also in light of potential future treatment options for patients with EDs.